The Influence of the Principal’s Academic Supervision and the Work Ethic of Teachers on Educational Quality - Gunarti, Gunarti; Hidayat, Sholeh; Risdianto, Eko; Ratnaya, I Gede (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
The aim of this study is to investigate and assess whether the academic supervision of the principal and the work ethic of the teachers have an influence on the quality of education. This study was carried out at SMA Negeri 10 Palembang, and the research method employed was descriptive analysis using a quantitative approach. The participants in this study are 60 instructors from SMA Negeri 10 Palembang. Data gathering methods include providing questionnaires that reflect all variables. The data analysis strategy used in this study is simple regression and multiple regression with SPSS. The findings revealed that there was a substantial effect of the principal's academic supervision variable on the quality of education, as well as a positive and significant influence of the principal's supervision and the teacher's work ethic on the quality of education at SMA Negeri 10 Palembang. The findings of this study are likely to aid teachers in the design of the learning process.